Construct validity of the Trail Making Test: Role of task-switching, working memory, inhibition/interference control, and visuomotor abilities - SÁNCHEZ-CUBILLO, I.; PERIÁÑEZ, J.A.; ADROVER-ROIG, D.; RODRÍGUEZ-SÁNCHEZ, J.M.; RÍOS-LAGO, M.; TIRAPU, J.; BARCELÓ, F. (Journal of the International Neuropsychological Society, 2009)
The aim of this study was to clarify which cognitive mechanisms underlie Trail Making Test (TMT) direct and derived scores. A comprehensive review of the literature on the topic was carried out to clarify which cognitive factors had been related to TMT performance. Following the review, we explored the relative contribution from working memory, inhibition/interference control, task-switching ability, and visuomotor speed to TMT performance. Forty-one healthy old subjects participated in the study and performed a battery of neuropsychological tests including the TMT, the Digit Symbol subtest [Wechsler Adult Intelligence Scale (Third Version) (WAIS-III)], a Finger Tapping Test, the Digits Forward and Backward subtests (WAIS-III), Stroop Test, and a task-switching paradigm inspired in the Wisconsin Card Sorting Test. Correlation and regression analyses were used in order to clarify the joint and unique contributions from different cognitive factors to the prediction of TMT scores. The results suggest that TMT-A requires mainly visuoperceptual abilities, TMT-B reflects primarily working memory and secondarily task-switching ability, while B-A minimizes visuoperceptual and working memory demands, providing a relatively pure indicator of executive control abilities. (JINS, 2009, 15, 438–450.)